Pemikiran Politik Islam - Qonita Fathin Suhaila; Wafiq Azizah Rangkuti; Nurul Izzati; Marzuki Manurung (Journal of Innovative and Creativity, 2025)
The history of thought in the field of Islamic sources of teachings, including the Qur'an, Hadith, Ijma', and Qiyas, plays an important role in the development of Islamic law and thought throughout time. Along with social, political, and economic changes, the relevance of these sources of teachings in fascing the challenges of the times is increasingly important to understand. This study aims to examine the contribution of the history of thought in developing the Islamic legal system and responding to the challenges of the modern era. The method used in this study is a qualitative approach with a library research type, which relies on literature studies from various primary and secondary sources. The results of the study show that the process of tanzilul Al-Qur'an and codification of Hadith in a historical perspective shows how the revelation of the Qur'an was revealed systematically and how the Hadith was collected to maintain the authenticity of the sources of Islamic teachings, so that it becomes the main guideline in determining Islamic law. In dealing with legal problems that are not explicitly explained in the basic texts, scholars then developed the Ijma' and Qiyas methods as ijtihad methods to find contextual legal solutions.